Persistence of congenital penile frenulum in male cat: Case report - Garcia, Juliana Chieco Jeronymo; da Silva, Matheus Felipe [UNESP]; Angrimani, Daniel de Souza Ramos [UNESP] (Universidade de São Paulo. Agência de Bibliotecas e Coleções Digitais, 2019)
The penile frenulum is a thin strip of connective tissue that connects the penis glans to the foreskin. Due to the few number of reports of this condition, this work reports the occurrence of persistent penile frenulum in a mixed breed domestic cat, of seven months old and 5.2 kg. In this particular case, penile frenulum was an incidental finding during clinical examination. The animal was in puberty, characterizing the penile frenulum. The resolution of the case occurred spontaneously prior to elective orchiectomy. Thus, the changes observed in the penis due to congenital alteration in cats are described in this report.
Persistência de frênulo peniano congênito em gato macho: Relato de caso
Keywords: Animal reproduction; Feline; Penile frenulum